The Influence of Social Media Influencer, Product Quality, Price, and Brand Image on Purchase Decisions for Local Perfume SAFF&Co - Muhammad Ariq Ikhsan; Hartoyo Hartoyo; Netti Tinaprillia (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The perfume industry in Indonesia has grown significantly as public awareness of self-care increases, supported by lifestyle developments among Millennials and Generation Z and the influence of social media. Saff & Co.is a local brand that has shown positive growth, although its e-commerce market share fluctuated during 2022–2025. This study aims to identify consumer characteristics, perfume consumption and purchasing behavior; analyze the influence of price, product quality, brand image, and social media influencers (SMI) on purchasing decisions; examine the effect of SMI on brand image; and assess the mediating role of brand image between SMI and purchasing decisions. Data were collected from 167 respondents through an online survey using voluntary sampling in the Greater Jakarta (Jabodetabek) area. Descriptive analysis shows that most respondents learned about Saff & Co.through social media, select perfumes primarily based on scent, and prioritize product quality over other factors when purchasing. SEM analysis indicates that product quality, price, and brand image significantly influence purchasing decisions. SMI do not directly affect purchasing decisions but have a significant indirect effect through brand image. The company should focus on improving product quality, managing prices that align with consumer value perceptions, and selecting credible influencers to consistently strengthen brand image.